Cover Image. Issue 2 (30th January 2020) - Kang, Liane J.; Vu, Khanh N.; Koleva, Petya T.; Field, Catherine J.; Chow, Angela; Azad, Meghan B.; Becker, Allan B.; Mandhane, Piushkumar J.; Moraes, Theo J.; Sears, Malcolm R.; Lefebvre, Diana L.; Turvey, Stuart E.; et al.
Abstract : The cover image is based on the Original Article Maternal psychological distress before birth influences gut immunity in mid‐infancy by Liane J Kang et al., https://doi.org/10.1111/cea.13551 . Supported By: CHILD Cohort Study, AllerGen NCE & CIHR